2016
DOI: 10.1039/c6cc03471c
|View full text |Cite
|
Sign up to set email alerts
|

Ship in a breakable bottle: fluoride-induced release of an organic molecule from a Pr(iii)-linked molecular cage

Abstract: A 3-dimensional networked molecular cage, , has been synthesized. This macrocycle-based framework was prepared from a solvothermal reaction involving a flexible organic building block, calix[4]pyrrole dibenzoic acid (H2), and Pr(NO3)3·6H2O. A unique feature of is that it retains free calix[4]pyrrole molecules in the framework pores. Treatment with a fluoride anion source serves to destroy the network and allows release of the organic guest. The net result is a 'molecular ship' in a 'breakable bottle'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…In previous studies we found that calix[4]pyrrole (C[4]P) could be exploited as a secondary building unit (SBU) in conjunction with praseodymium(III) to create a metal-macrocycle framework (MMF). 20 The chemically responsive behaviour between Pr(III) and fluoride anion was described, but no photochemical properties were observed. We thus envisaged that marriage of the uranyl cation with a judiciously designed calix[4]pyrrole might furnish new cage frameworks that would respond to uranyl-mediated photochemistry.…”
mentioning
confidence: 99%
“…In previous studies we found that calix[4]pyrrole (C[4]P) could be exploited as a secondary building unit (SBU) in conjunction with praseodymium(III) to create a metal-macrocycle framework (MMF). 20 The chemically responsive behaviour between Pr(III) and fluoride anion was described, but no photochemical properties were observed. We thus envisaged that marriage of the uranyl cation with a judiciously designed calix[4]pyrrole might furnish new cage frameworks that would respond to uranyl-mediated photochemistry.…”
mentioning
confidence: 99%
“…anions), several trans-'two-wall' C4Ps have been reported to adopt the 1,2-alternate conformation in the solid state in the absence of a guest. 33,35,[41][42][43] These observations led us to suggest that the 1,2-alternate form may be the most stable conformation for trans-'two-wall' diaryl C4Ps. To the extent this inference is true, we conclude that the interaction with PZDO does not induce a conformational change in the case of receptor 4.…”
Section: Solid-state Complex Formationmentioning
confidence: 99%
“…Destacam-se ainda os trabalhos pioneiros que incidem sobre a preparação de MOFs utilizando novos análogos porfirínicos, que incluem o uso de hidroporfirinas como clorinas [51], porfirinas N-confusas [52], ftalocianinas [53], calix [4]pirróis [54,55] e corróis [56].…”
Section: Sensores óTicos Baseados Em Mofs Porfirínicosunclassified